Value of Assessing Personal, Organizational, and Community Impacts of Extension Volunteer Programs - Rebecca Harrington; Tillie Good; Kandi O'Neil; Samantha Grant; Sarah Maass; Rachelle Vettern; Patricia McGlaughlin ([TEST] Journal of Extension, 2021)
Extension volunteers demonstrate personal, organizational, and community benefits. Our group of Extension professionals in the North Central Region applied these three levels of benefit to gather quantitative and qualitative data in a comprehensive evaluation of volunteer impact. Survey responses were received from 2,978 4-H youth development volunteers in 12 states. A mixed-methods approach, such as the one we used, can provide Extension professionals with evidence to communicate the value of volunteer programs and improve their practice in volunteer systems management.
Keywords: Volunteer; impact evaluation; public value; benefits; 4-H